Superparamagnetic Iron Oxide Nanoparticles (SPIONs): Synthesis and Surface Modification Techniques for use with MRI and Other Biomedical Applications - Yoffe, Serge; Leshuk, Tim; Everett, Perry; Gu, Frank (Current Pharmaceutical Design, 2013)
Superparamagnetic iron oxide nanoparticles (SPIONs) comprise a fundamental technology class within the emerging field of nanomedicine, and have been extensively researched for cancer imaging and therapy. This review article will discuss the chemistry and design considerations associated with the synthesis of SPIONs and their incorporation into pharmaceutical formulations. Specific synthesis methods discussed include coprecipitation, thermal decomposition, microemulsion and solvothermal synthesis, as well as surface treatments and encapsulations to improve the nanoparticle biocompatibility and efficacy. Emerging applications of novel particle designs as MRI contrast agents are also discussed.
Keywords: microemulsion